Sustainable Routes for the Synthesis of Renewable Adipic Acid from Biomass Derivatives. Issue 1 (30th November 2021) - Lang, Man; Li, Hao
Abstract: Adipic acid (AA) is a key industrial dicarboxylic acid intermediate used in nylon manufacturing. Unfortunately, the traditional process technology is accompanied by serious environmental pollution. Given the growing demand for adipic acid and the desire to reduce its negative impact on the environment, considerable efforts have been devoted to developing more green and friendly routes. This Review is focused on the latest advances in the sustainable preparation of AA from biomass‐based platform molecules, including 5‐hydroxymethylfufural, glucose, γ‐valerolactone, and phenolic compounds, through biocatalysis, chemocatalysis, and the combination of both. Additionally, the development of state‐of‐the‐art catalysts for different catalytic systems systematically is discussed and summarized, as well as their reaction mechanisms. Finally, the prospects for all preparation routes are critically evaluated and key technical challenges in the development of green and sustainable processes for the manufacture of AA are highlighted. It is hoped that the green adipic acid synthesis pathways presented can provide insights and guidance for further research into other industrial processes for the production of nylon precursors in the future. Abstract : A platform for sustainability : Adipic acid is a versatile dicarboxylic acid used in nylon manufacturing and an array of other processes in the chemical, pharmaceutical, and food industries. This Review summarizes and discusses recent advances in the synthesis of renewable adipic acid from bio‐based platform molecules by chemical, biological, and biochemical methods.